Building construction and materials - Gurcharan Singh (Standard Book House, 2012)
The size of the present book has been enlarged considerably easily it has been updated according to the latest trends on valuable suggestions and specifications from learned professors of various engineering colleges. Basic engineering material like stone, bricks, lime, cement, timber and iron has been also included in it.